1969
DOI: 10.1104/pp.44.5.662
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Rate of CO2 Evolution by Green Leaves in Light

Abstract: Abstract. The rate of CO,, evolution in light by green leaves was determined by 2 methods in a closed system of gas analysis and by measuring the amount of CO, evolved in-to a CO., free air stream in an open system. All methods gave similar results under comparable oonditions.A light stimulated CO., evolution from green leaves was found in all the plant species studied except corn where there was no apparent CO., evolution in the light.The magnitude of CO., evolution in light was markedly dependent on air flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1969
1969
1979
1979

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…It has been reported that the rates of CO2 evolution by green leaves in light are affected by both O, concentration (6, 9, 11, 14, 29) and light intensity (3,6,15, 17,18,27). Decker (3) has shown that the post-illumination CO., outburst from tobacco at 33.5' was 3 times as large as that at 17.50 and Zelitch (34) has also shown that CO., evolution in light increases with a temperature increase from 250 to 350.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the rates of CO2 evolution by green leaves in light are affected by both O, concentration (6, 9, 11, 14, 29) and light intensity (3,6,15, 17,18,27). Decker (3) has shown that the post-illumination CO., outburst from tobacco at 33.5' was 3 times as large as that at 17.50 and Zelitch (34) has also shown that CO., evolution in light increases with a temperature increase from 250 to 350.…”
Section: Introductionmentioning
confidence: 99%
“…Additional knowledge would be of interest since there is increasing evidence to in.dicate that in green 'leaves the processes leading to the evolution of CO., in light and in darkness mav be different (6,9,11,17,23 35-day old watermelon and eggplants were used. The closed and the open systems of gas analysis were the same as described previously ( 15,16). The closed system was used to study the magnitude of the post-illumination CO. outburst, the CO., compen'sation point, and the effect of CO) concen,tration on -the rate of apparent photosynthesis at various temperattures.…”
mentioning
confidence: 99%
“…Under these conditions, most methods for detecting photorespiration would indicate its absence, for they depend on the maintenance of an internal CO2 level significantly above zero. A low internal CO2 level could account for the nearly equimolar uptake of "4CO2 and 'CO., by maize exposed to low (atmospheric) CO2 levels (15,45). Under these conditions the diffusion of each CO2 species would be directly proportional to its atmospheric concentration if its internal concentration were essentially nil.…”
Section: Resultsmentioning
confidence: 99%
“…Its CO2 compensation concentration (F ) approaches zero at temperatures less than 30 C (28,29,42) and is unaffected by 02 concentration (7,10); it releases little or no CO2 to CO2-free air (8,30) or even to C02-free oxygen (48); it fails to exhibit a CO, burst upon darkening (6,10,42); its net photosynthetic rate is not stimulated by lowering the ambient 02 concentration from 21 to 2% (3,5,7,14,18); and it does not depress the specific radioactivity of 14C during photosynthetic CO2 fixation (15,45). The absence of these external photorespiratory indices can be interpreted in two ways: maize either lacks photorespiration altogether, or it recycles photorespiratory CO2 with considerable efficiency.…”
mentioning
confidence: 99%
“…There is evidence that weak illumination curtails the dark respiration process and simultaneously initiates light-dependent photorespiration (Fock and Egle 1966;Forrester, et al 1966;Poskuta 1968a;1968b;Poskuta, et al 1967;Tregunna, et al 1966). Carbon dioxide (Hew, et al 1969;Holmgren and Jarvis 1967) and oxy gen (Govindjee, et al 1963;Hoch, et al, 1963) measurements indicate that dark respiration exceeds photorespiration at low light intensities but that as light intensity increases photorespiration is accelerated and dark respiration de creases and eventually ceases. Jackson and Volk (1970) state that this observation is in accord with the concept that low light is sufficient to curtail dark respiration while the initiation of photorespiration reguires a higher light inten sity and is responsive to increasing rates of photosynthesis.…”
Section: Distribution Of Assimilatementioning
confidence: 99%